Distribution and morphometry of shallow lakes in a temperate zone (Buenos Aires Province, Argentina) - Bohn, Vanesa Yael (2011)
We have developed a database of water bodies to characterise and assess the distribution and morphometry of Pampean shallow lakes and reservoirs in a temperate zone (Buenos Aires Province, Argentina). In the study area, there are over 2000 shallow lakes with a mean area <1 km2. The spatial variation in the shallow lakes studied is related to alternating periods of different hydrological conditions and the flatness of the Pampean landscape. The aim of this research is both to establish a classification system for the shallow lakes in the studied area and to evaluate the influence of rainfall regime on their morphometry. This classification system will provide a typological reference against which the ecological state of waters can be assessed. The spatial distribution, morphometry and changes in the size of the shallow lakes in southern Buenos Aires were studied during two periods: a normal (a year with average rainfall) and a wet year. A Geographic Information System (GIS) as well as satellite imaging and Digital Elevation Model (DEM) data were used to calculate the morphometry of the shallow lakes and observe changes over time. Based on climatic criteria, geomorphology, soils and hydrology, four groups of lakes were identified: 1) plain and plateau lakes (constituting the highest proportion of circular shallow lakes), 2) artificial lakes (a category constituted solely of the only water reservoir in the studied area), 3) coastal plain lakes characterised by a Coastal Line Development (CLD) < 2 and 4) coastal plain lakes characterised by a CLD >2. In the last two cases, geomorphology determines the morphometry and location of these shallow lakes. The development of numerous water bodies with areas <1 km2 caused a significant increase in the number of water bodies during the wet year. The areal coverage and density of lakes is lowest in the western plateau zones, low near the hills, moderate in the centre of the study area and high in the eastern plains.